Some aspects of Diglossia in Arab, Georgian and German Languages - Jordania, Alex (Actual Problems of Kartvelology, 2025)
Georgia is a member of the Council of the European Union, and there are Council of Europe recommendations that schools should be established in the "regional or minority language", the best works of literature should be translated, newspapers should be established, and television broadcasting should be created. However, the Council of Europe recommendations do not call on Georgians to recognize Svan, Megrelian, or Laz dialects as regional languages; this should be the will of Georgians.